La educación en alimentación - Jiménez Arrunátegui, Yadira Rosa (2012)
The present article develops the communityand family approach of food to present theproposal for Education in Nutrition fromthe educational institutions of regular basiccentered on experience of Social Projectionof the Nutrition and Dietetics Program at the“Universidad Femenina del Sagrado Corazón- UNIFÉ”.